2021
DOI: 10.1186/s40659-021-00366-y
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of mesenchymal stem cells in treating osteoporosis

Abstract: Osteoporosis (OP), a common systemic metabolic bone disease, is characterized by low bone mass, increasing bone fragility and a high risk of fracture. At present, the clinical treatment of OP mainly involves anti-bone resorption drugs and anabolic agents for bone, but their long-term use can cause serious side effects. The development of stem cell therapy and regenerative medicine has provided a new approach to the clinical treatment of various diseases, even with a hope for cure. Recently, the therapeutic adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 116 publications
(119 reference statements)
2
10
0
Order By: Relevance
“…62,63 As for the clinical applications of Ad-MSCs, there is growing number of researchers start to explore the potential use of MSCs from various sources in the treatment of osteoporosis clinically. 64,65 Previous studies showed that Ad-MSCs can enhance bone regeneration in ovariectomized mice, 66 rabbits 67 or through its capacity to differentiate down the osteogenic lineage, 68 similar to this current study. Although the clinical studies of Ad-MSCs utility in treatment of osteoporosis is still scarce, however, Ad-MSCs showed some success in treatment of microfractures, 69 bone defects 70 and osteoarthritis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…62,63 As for the clinical applications of Ad-MSCs, there is growing number of researchers start to explore the potential use of MSCs from various sources in the treatment of osteoporosis clinically. 64,65 Previous studies showed that Ad-MSCs can enhance bone regeneration in ovariectomized mice, 66 rabbits 67 or through its capacity to differentiate down the osteogenic lineage, 68 similar to this current study. Although the clinical studies of Ad-MSCs utility in treatment of osteoporosis is still scarce, however, Ad-MSCs showed some success in treatment of microfractures, 69 bone defects 70 and osteoarthritis.…”
Section: Discussionsupporting
confidence: 83%
“…As for the clinical applications of Ad‐MSCs, there is growing number of researchers start to explore the potential use of MSCs from various sources in the treatment of osteoporosis clinically 64,65 . Previous studies showed that Ad‐MSCs can enhance bone regeneration in ovariectomized mice, 66 rabbits 67 or through its capacity to differentiate down the osteogenic lineage, 68 similar to this current study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“… 79 However, some safety issues related to the long course of treatment cannot be ignored, such as the risk of local infection, abnormal immune responses, and the excessive accumulation of amyloid-β, in particular the development of tumor induction by chromosomal abnormalities, which cannot be completely avoided based on the MSC characteristics and the effect of external conditions. 80 …”
Section: Safety Of Mscsmentioning
confidence: 99%
“…In recent years, gene therapy and mesenchymal stem cell (MSC) therapy has been developed as novel regenerative medicine treatments (9,10). MSC therapy may have a bright future in the treatment of osteoporosis (11,12). MSCs appear to be multipotent stem cells, which may self-renew and specialize in multiple directions, and they serve a vital role in tissue regeneration and regenerative medicine (9).…”
Section: Introductionmentioning
confidence: 99%